Issues in Contemporary Orthodontics - Bourzgui, Farid (IntechOpen, 2015)
Issues in Contemporary Orthodontics is a contribution to the ongoing debate in orthodontics, a discipline of continuous evolution, drawing from new technology and collective experience, to better meet the needs of students, residents, and practitioners of orthodontics. The book provides a comprehensive view of the major issues in orthodontics that have featured in recent debates. Abroad variety of topics is covered, including the impact of malocclusion, risk management and treatment, and innovation in orthodontics.